Electronic interactive panel as a modern mean of professional training of future physics teachers - Tokarev , P. (New Collegium, 2020)
The article gives a theoretical justification for the effectiveness of the interactive panel as a modern mean of preparing future physics teachers for professional activities. The technical and didactic properties of the interactive whiteboard and the principles of its use are singled out. Based on the analysis of psychological, pedagogical and professional literature, the essence of the concepts "teaching aids", "technical teaching aids", "interactive teaching aids" is revealed. The author’s definition of the concept of "learning tools" is given. The classification of the concept of "learning tools" on various grounds: the nature of the representation of the surrounding reality, the application in the educational process. The article describes the difference between the concepts of "electronic interactive whiteboard" and "electronic interactive panel". The didactic possibilities of electronic interactive panels as an effective teaching tool used to prepare future physics teachers for professional activities are highlighted, the advantages of their use in the educational process are described. The didactic functions of the electronic interactive panel – managerial, adaptive, informative, integrative, interactive, motivational, communicative, developing and educational are considered. The article describes the possibilities of using an electronic interactive panel used in the professional activities of a physics teacher, which will provide increased attention, increase motivation for learning and cognitive activity, activation of mental activity. The problems which are solved by mean of use of the electronic interactive panel in the course of teaching of physics in establishments of higher education are considered.